Small ruminant production in smallholder and pastoral/extensive farming systems in Kenya - Kosgey, I.S.; Rowlands, G.J.; Arendonk, Johan A.M. van; Baker, R.L. (Elsevier, 2008)
A survey was conducted by way of personal interviews with 562 respondents comprising 459 farmers and 103 butchers/traders in selected districts in the central and western parts of Kenya, consisting of three predominantly smallholder and four predominantly pastoral/extensive districts. The study aimed to provide a better understanding of smallholder and pastoral/extensive sheep and goat farming systems in the tropics, by taking Kenya as an example. The results showed that 58% of the pastoral/extensive farmers and 46% of the smallholders indicated livestock as their main activity. Small ruminants ranked closely behind cattle in their importance. Thirty-four percent of the households kept only sheep, 18% only goats and 48% both species. The survey demonstrated the relative importance to the farmers of tangible benefits of farming sheep and goats (e.g., regular cash income, meat, manure and, in the case of goats, milk) versus intangible benefits (e.g., the role of small ruminants as an insurance against emergencies). Regular cash income and an insurance against emergencies were the highest priorities. Seventy-eight percent of the farmers reported animal sales over the previous 12 months of the survey date. Of these sales, the income was spent on school fees (32%), purchase of food (22%), farm investment (18%), medical expenses (10%), off-farm investment (9%), social activities (5%) and re-stocking (4%). Indigenous genotypes were predominant among the pastoralists and mixed crosses predominant among the smallholders. A range of traits: growth rate, body size, body shape, drought tolerance, meat quality, fertility, disease and heat tolerance, prolificacy and temperament were all considered important for both sheep and goats in both farming systems and across the different genotypes. Compared with other pure breeds, the Red Maasai sheep and the Small East African goats were rated poorly in terms of body size, body shape, growth and fertility, but highly in terms of drought and (for the Red Maasai) heat tolerance by both smallholder and pastoralist farmers. In general, crosses were perceived less favourably than indigenous pure breeds. Body size and performance ranked as the most important traits in the choice of breeding males. Approximately half the farmers inherited their males, reared them on the farm and kept them for an average of 2-3 years. Uncontrolled mating within the household's flock was predominant in both farming systems. Over 98% of the farmers reported incidence of disease, especially pneumonia (in pastoral/extensive areas), helminthosis, tick-borne diseases, diarrhoea and foot-rot. Over 95% of the farmers fed supplements in both dry and wet seasons. Pure exotic and indigenous×exotic genotypes fetched higher prices than indigenous genotypes due to their heavier body weight. In conclusion, the foregoing issues need attention in genetic improvement programmes, with more emphasis on the conservation and utilisation of indigenous small ruminant genotypes.